A comprehensive review on roles of electrochemical approaches in drug delivery - Ali R. Jalalvand; Mohammad Mehdi Karami (Sensing and Bio-Sensing Research)
The advancement of drug delivery systems (DDS) has significantly enhanced the efficacy and safety of therapeutic agents addressing limitations such as poor bioavailability and non-specific distribution associated with traditional methods. This article provides a comprehensive review of the role of electrochemical approaches in DDS, highlighting their precision, minimally invasive nature and ability to provide targeted and localized therapy. Electrochemical methods including voltammetry, amperometry and potentiometry offer unparalleled control over drug release kinetics and distribution, presenting significant advantages for the treatment of chronic and complex diseases like cancer, cardiovascular disorders, and neurological conditions. The integration of biotechnology, materials science and nanotechnology has led to the development of sophisticated DDS that respond to specific biological signals. This review discusses the fundamental principles of electrochemistry, various electrochemical techniques, and their applications in DDS alongside current innovations and future research directions in the field. The potential of electrochemical approaches to revolutionize drug delivery by providing precise, controlled, and targeted therapeutic interventions is emphasized, underscoring their growing importance in personalized medicine and future biomedical applications.